2h+h+4=10

Simple and best practice solution for 2h+h+4=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2h+h+4=10 equation:


Simplifying
2h + h + 4 = 10

Reorder the terms:
4 + 2h + h = 10

Combine like terms: 2h + h = 3h
4 + 3h = 10

Solving
4 + 3h = 10

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 3h = 10 + -4

Combine like terms: 4 + -4 = 0
0 + 3h = 10 + -4
3h = 10 + -4

Combine like terms: 10 + -4 = 6
3h = 6

Divide each side by '3'.
h = 2

Simplifying
h = 2

See similar equations:

| X^3-7x^2+9x-63=0 | | x+x+8= | | 12+3(2y-5)=25+4y | | m+8n-5m-3n= | | P-6=24-2P | | 2x+24=0.285 | | -ax=b | | 2x+24=0.28 | | 8x+65-5x-75=35-63x | | 3x^4+9x^2+6=0 | | s=(4000)+71 | | 120overn=10 | | p(x)=-13x^2+1430x-23.400 | | 18-2r+4= | | s-26=(9)(5) | | h=5vt+16t^2 | | 18-2r= | | 12h-12=10h+4-2n | | (18/(-21))=(6g+4k)/((-6g)+(4k))/((-6g)-(3k)) | | 18-2r-4= | | 7x-8=4x | | 5-26=(9)(5) | | 5p+6(1-10p)=-49 | | 6x+10-12=3x+8 | | 1+e=21 | | a^2+8a=-9 | | 0.008(x+20)-0.03x=2.4 | | 4x-18=4x-6 | | -4(r+6)=-46 | | s=5h+5z | | 5s+s=78 | | 9y^2+36y-124=0 |

Equations solver categories